The Meaning Of Ultra Qui Judicat Principle And The Validity Of The Verdict In Criminal Cases - Suwitno Y IMRAN; Sudarsono SUDARSONO; I Nyoman NURJAYA; Nurini APRILIANDA (International Journal of Environmental, Sustainability, and Social Science, 2022)
The prohibition for judges to not sentence the defendant if the act is not described carefully, clearly and completely in the indictment of the public prosecutor, it turns out that in practice in court, there are judges who deviate from the article charged by the public prosecutor. The judge's action is called the ultra qui judicat principle, that is deviating from what was charged. The main problem in this paper is about the meaning of the Ultra Qui Judicat Principle and the Validity of Decisions in Criminal Cases. The main problems will be analyzed using normative legal research methods using a case approach and data sources from laws and regulations. The results show that the Ultra Qui Judicat Principle is an act of a judge deciding a case by placing justice as the goal of being able to deviate from the indictment of the public prosecutor based on the facts of the trial. This principle then has a specificity in the form of this principle being devoted to judges in deciding criminal cases, the use of this principle emphasizes the justice of judges in deciding criminal cases, and the scope of this principle is found in the facts of the trial. Furthermore, in exploring the meaning or value of the Ultra Qui Judicat principle, it is done by analyzing a judge's verdict, approach to legal expert opinion, and reviewing the legislation.